Proprotein convertase subtilisin/kexin type 9 deficiency in extrahepatic tissues: emerging considerations - Lu, Fengyuan; Li, En; Yang, Xiaoyu (Frontiers in Pharmacology, 2024)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) is primarily secreted by hepatocytes. PCSK9 is critical in liver low-density lipoprotein receptors (LDLRs) metabolism. In addition to its hepatocellular presence, PCSK9 has also been detected in cardiac, cerebral, islet, renal, adipose, and other tissues. Once perceived primarily as a "harmful factor," PCSK9 has been a focal point for the targeted inhibition of both systemic circulation and localized tissues to treat diseases. However, PCSK9 also contributes to the maintenance of normal physiological functions in numerous extrahepatic tissues, encompassing both LDLR-dependent and -independent pathways. Consequently, PCSK9 deficiency may harm extrahepatic tissues in close association with several pathophysiological processes, such as lipid accumulation, mitochondrial impairment, insulin resistance, and abnormal neural differentiation. This review encapsulates the beneficial effects of PCSK9 on the physiological processes and potential disorders arising from PCSK9 deficiency in extrahepatic tissues. This review also provides a comprehensive analysis of the disparities between experimental and clinical research findings regarding the potential harm associated with PCSK9 deficiency. The aim is to improve the current understanding of the diverse effects of PCSK9 inhibition.